Thermo stabilisation of poly (butylene adipate-co-terephthalate) - Chaves,Rodrigo Paulino (2016)
Abstract Poly (butylene adipate-co-terephthalate) - PBAT is a synthetic biodegradable polymer commonly used for plastic film production from neat polymer or nanocomposites. The PBAT is submitted to high temperatures and shear rate during its processing. In the present study, the thermo stabilisation of PBAT by the addition of two types of stabilisers was studied using a torque rheometer at 60 rpm and two levels of temperature. The stabilisers were used as master batches with a percentage of 10% by weight of additive in the PBAT. Molecular weight, torque values after 10 minutes of mixing, and absorbance at 400 nm were used to evaluate the process of stabilisation. The primary and secondary antioxidant used here had a positive effect on both processing temperatures, 180 and 200 °C. The best results indicate that the primary antioxidant could be used alone to protect PBAT against thermodegradation reactions.